2020
DOI: 10.1186/s40249-020-00722-2
|View full text |Cite
|
Sign up to set email alerts
|

Massive migration promotes the early spread of COVID-19 in China: a study based on a scale-free network

Abstract: Background: The coronavirus disease 2019 (COVID-19) epidemic met coincidentally with massive migration before Lunar New Year in China in early 2020. This study is to investigate the relationship between the massive migration and the coronavirus disease 2019 (COVID-19) epidemic in China. Methods: The epidemic data between January 25th and February 15th and migration data between Jan 1st and Jan 24th were collected from the official websites. Using the R package WGCNA, we established a scale-free network of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Studies have shown that analyzing population out ow distribution based on mobile phone data in Wuhan can accurately identify and predict high-risk areas at an early stage [30]. The pandemic severity in other regions was primarily affected by emigration from Wuhan [31]. The analysis of the movement trajectory of con rmed cases presented in this study also demonstrated that the ow of con rmed cases originated from Wuhan, and the degree centrality showed the spread of the COVID-19 epidemic has evident spatial agglomeration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that analyzing population out ow distribution based on mobile phone data in Wuhan can accurately identify and predict high-risk areas at an early stage [30]. The pandemic severity in other regions was primarily affected by emigration from Wuhan [31]. The analysis of the movement trajectory of con rmed cases presented in this study also demonstrated that the ow of con rmed cases originated from Wuhan, and the degree centrality showed the spread of the COVID-19 epidemic has evident spatial agglomeration.…”
Section: Discussionmentioning
confidence: 99%
“…Since massive migration is considered to promote the early spread of COVID-19 in China and China's practices with isolation of patients and quarantine of persons with close contacts [31,32], the early admissions of all patients and widespread antiviral therapy might be contributable for the benign epidemiological outcome of this local epidemic episode. Early admissions and early/widespread antiviral therapy might be helpful for the prevention of community and health worker infections.…”
Section: Discussionmentioning
confidence: 99%
“…The scale-free networks are networks whose distribution degree follows a power law distribution with an exponent between 2 and 3. The study of epidemics and disease dynamics on scale-free networks is a relevant theoretical issue [47], because this networks are a model for the spread of sexually transmitted diseases (see for instance [48]) or a model to explain the early spread of COVID-19 in China (see [49]). Many works that address this type of network in spread of disease can be found in the literature.…”
Section: Scale-free Networkmentioning
confidence: 99%